(untitled) (Global Journal of Science Frontier Research, 2020)
The article is devoted to the topical problem of forming a hybrid spatial environment as a multiagent system. In the study have been identify the innovative concepts of the forming an architectural space as a multi-agent system that uses the technological innovations of the future. A forward-looking approach to the organization of spatial habitat as a multi-component system is propos. The leading approach to the study of this problem is based on analytical research methods: comprehensive design of the object as a system, the method of structural analysis, and the information technique. As a result, concepts of creating an artificial habitat using hybridization properties have been identify. Trends in modeling new types of spaces based on the idea of self-organization of the evolving system have been identifying.